Land Ownership without Legal Certainty: Problems of Unregistered Land Rights - Mofu, Marselina Ivony (Jurnal Hukum dan Keadilan, 2026)
Land, as a source of life and an instrument of social justice, holds a fundamental position in the Indonesian legal system. Although land registration is regulated by the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997, practice shows that many land rights remain unregistered, giving rise to legal certainty issues. This article aims to analyze the legal status of unregistered land within the national land system and formulate a reconstruction of legal protection to address the existing normative ambiguity. This study uses a normative legal research method with a statutory, conceptual, and case-based approach, analyzed qualitatively and prescriptively. The results indicate that the ambiguity of norms regarding the legal consequences of unregistered land and the status of non-certificate evidence has weakened the function of registration as an instrument of legal certainty. A negative publication system with a positive tendency results in certificates only having strong but not absolute evidentiary force, while unregistered land is vulnerable to disputes. Normative reconstruction is needed through affirming the deadline and legal consequences of registration, strengthening the principle of good faith, harmonizing with civil evidence law, and strengthening the publication system through digitization and integration of land data. This reformulation has implications for preventing agrarian conflicts, increasing state legitimacy, and realizing just legal certainty.